The increasing isolation of Serratia species from clinical specimens. - Brooks, H. J. (Cambridge University Press, 1979)
A 14-month survey was undertaken in a diagnostic bacteriology laboratory to determine the incidence of Serratia spp. in routine clinical specimens. Gram-negative organisms with enterobacteria-like colonies were tested by a simple screening procedure. Fifty-eight strains of S. marcescens and two strains of S. liquefaciens were isolated from 59 patients. The strains were usually non-pigmented and exhibited multiple antibiotic resistance. Serotyping and determination of bacteriocine sensitivity patterns revealed that the majority of infections were sporadic, although episodes of cross-infection did occur. S. marcescens was considered to contribute significantly to morbidity and mortality in 53% of patients and appears to be of increasing importance in hospital-acquired infections.